Analisa Transnational Advocacy Network : Transnasionalisme Redress Movement for Comfort Women di Negara Barat oleh The Korean Council 2015-2021 - Helga Prashernanda; Mohamad Rosyidin; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2022)
Within the history of Japanese Colonization, follows establishment of Japanese Military Sexual System. Japanese action trigger transnational movement who gave demands for Japan to redress, but have not accomplished until this time. There are attempts to made an issue’s settlement through Japan-ROK Agreement 2015, however The Redress Movement for Comfort Women in western country still giving their efforts, and there is fresh establishment of new NGO after Agreement accomplished. The purpose of this research is to examine transnationalization’s process of Redress Movement for Comfort Women in the West Country. To analyze the process of transnationalism of Redress Movement for Comfort Women, this research use Transnational Advocacy Network (TAN) approach and Boomerang Pattern Concept. This research have two argument, first argument saying that transnationalism of Redress Movement for Comfort Women in western countries are caused by implementation of TAN and Boomerang Pattern by The Korean Council. The Korean Council must implementing TAN Strategy due to Blockage has given by the Government of Japan and South Korea.